New reports of Capnogryllacris (Orthoptera: Gryllacrididae) from Yunnan, China - Peng, Xiaoyu; Yang, Zizhong; Bian, Xun (Zootaxa, 2021)
This paper deals with three species of Capnogryllacris from Yunnan, China. One new species, one new recorded species and the female sex of Capnogryllacris rufonotata (Li, Liu & Li, 2014) are described. All the examined specimens deposited in the Guangxi Normal University and Institute of Entomoceutics, Research, Dali University.